The adoption of the One Health approach to improve surveillance of venomous animal injury, vector-borne and zoonotic diseases in Foz do Iguaçu, Brazil. - André de Souza Leandro; Renata Defante Lopes; Caroline Amaral Martins; Açucena Veleh Rivas; Isaac da Silva; Sandro Roberto Galvão; Rafael Maciel- (Public Library of Science (PLoS), 2021)
Public health institutions with sectorized structure and low integration among field teams, old-fashioned practices such as paper-based storage system, and poorly qualified health agents have limited ability to conduct accurate surveillance and design effective timely interventions. Herein, we describe the steps taken by the Zoonosis Control Center of Foz do Iguaçu (CCZ-Foz) in the last 23 years to move from an archaic and sectorized structure to a modern and timely surveillance program embracing zoonotic diseases, venomous animal injuries, and vector-borne diseases epidemiology under the One Health approach. The full implementation of the One Health approach was based on 5 axes: (1) merging sectorized field teams; (2) adoption of digital solutions; (3) health agents empowerment and permanent capacitation; (4) social mobilization; and (5) active surveys. By doing so, notifications related to zoonotic diseases and venomous animals increased 10 and 21 times, respectively, with no impairment on arbovirus surveillance (major concern in the city). Open sources database (PostgreSQL) and software (QGis) are daily updated and create real-time maps to support timely decisions. The adoption of One Health approach increased preparedness for endemic diseases and reemerging and emerging threats such as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2).